2003
DOI: 10.1254/jphs.92.203
|View full text |Cite
|
Sign up to set email alerts
|

The Epoxy Group of Pramanicin Is Required for the Optimal Endothelium-Dependent Relaxation of Rat Aorta

Abstract: The vascular effects of a newly discovered anti-fungal agent, pramanicin (PMC), and its two analogues, PMC-A, in which the epoxy group is replaced by a - HC = CH - bond, and PMC-B, on which the diene is converted to the saturated (CH(2))(4)-derivative, respectively, were investigated in rat aorta. All three compounds caused an initial endothelial-dependent relaxation, which is prevented either by removal of endothelium or inclusion of the nitric oxide synthase inhibitor L-NAME. Upon prolonged incubation with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In this case, the chemical shift difference between 3a-e and 10a (ca. 2ppm) was larger than for the difference between 6b-e, 8 and 12 (ca.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In this case, the chemical shift difference between 3a-e and 10a (ca. 2ppm) was larger than for the difference between 6b-e, 8 and 12 (ca.…”
Section: Introductionmentioning
confidence: 73%
“…[10][11][12][13][14] There is no data related to its toxicity or mode of action. Other analogues of pramanicin (pramanicin A, TMC-260) are known, 8,15 and the isolation of the related virgaricin has been reported. 16 It has recently been recognised that existing strategies for the discovery of new antibacterials have not been effective, 17 probably as a result on over-reliance of combinatorial approaches leading to structurally narrow libraries, 18,19 and as a result there is an urgent need for the identification of novel leads for expanding the antibacterial drug development pipeline.…”
Section: Introductionmentioning
confidence: 99%
“…This compound is active against a number of fungi, including Cryptococcus neoformans . Pramanicin has also been found to disturb the vasorelaxation of dog carotid artery by selectively acting on the endothelial cells, causing relaxation through the endothelium-dependent nitric oxide pathway to activate endothelial nitric oxide synthase (169), and the epoxide is required for the optimal effects (170). It also activates caspases and induces apoptosis in Jurkat leukemia cells (171).…”
Section: αω-Sphingoids: “Two-headed” Sphingoid Base-like Compoundsmentioning
confidence: 99%
“…The ROESY correlations between OH-4/H-8 and H-5/H-8 indicated that OH-4 and H-5 were located on the same face of the molecule. This was supported by the similarities of 13 C NMR data in CD 3 OD (Table 1) between 1 and pramanicins, 7,8 indicating the same relative configurations at C-3, C-4 and C-5. In consequence, the relative stereochemistry of 1 in the g-lactam moiety was assigned to be the same as for pramanicins.…”
mentioning
confidence: 56%
“…7,12 Pramanicin has also been reported to cause endothelialdependent relaxation of rat aorta, although the activity of pramanicin A (in which the causative epoxide group was changed to a double bond) was weak. 13 While pramanicin's side-chains have two more carbons than 1, the side-chain carbon number of TMC-260, an IL-4 signal transduction inhibitor produced by Acremonium kiliense, 9 was the same as that of 1. Virgaricin produced by Virgaria sp.…”
mentioning
confidence: 99%